Analysis of Satisfaction Level of E- Correspondence System Users Using the End User Computing Satisfaction Method at Distrik Navigasi Tipe A Kelas II Benoa - Suta, I Gusti Lanang (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2023)
This study aims to determine the effect of the variables Content, Accuracy, Format, Ease of Use, and Timeliness on User Satisfaction in the implementation of the E-Correspondence system at Kantor Distrik Navigasi Tipe A Kelas II Benoa. The focus of this research is directed at the relationship of each independent variable to the dependent variable using the indicator approach of each variable, so that the results obtained can be used as material for evaluating information systems. The sample in this study amounted to 74 respondents who were selected by simple random sampling technique. The analysis technique used is Multiple Linear Regression Analysis with SPSS analysis tool. The results of the study show that all the hypotheses that have been formed have a positive and significant effect. This illustrates that the implementation of the system at Kantor Distrik Navigasi Tipe A Kelas II Benoa overall is good.